PENGARUH MODAL KERJA, TENAGA KERJA, DAN BIAYA BAHAN BAKU TERHADAP PENDAPATAN PENGUSAHA HOME INDUSTRI TEMPE DI DESA SEPANDE KECAMATAN CANDI KABUPATEN SIDOARJO - Krisna Fajar, Muhamad Ayub; Gunawan, Kunto Inggit (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2021)
This study aims to prove the effectiveness of working capital, labor, and raw material costs on the income of tempe home industry entrepreneurs in Sepande Village, Candi District, Sidoarjo Regency. This research method uses quantitative primary data, the data used is a questionnaire obtained from tempe entrepreneurs respondents. The data analysis tool in this study is the multiple linear regression method. The results of this study prove that partially or simultaneously there is a significant influence between working capital, labor and raw material costs on the income of tempe home industry entrepreneurs in Sepande Village, Candi District, Sidoarjo Regency. The variables of working capital (X1), labor (X2) and raw material costs (X3) with significant values, for the effect of working capital, labor, and raw material costs simultaneously on income (Y) of 0.04 < 0.05 and the calculated F value is 5,389 > Ftable 3,29, so it can be interpreted that the variables of working capital (X1), labor (X2), and raw material costs (X3) have a joint or simultaneous effect on the income (Y) of home industry entrepreneurs. tempeh in Sepande Village, Candi District, Sidoarjo Regency. With this it can be concluded that all hypotheses are accepted